Job satisfaction among selected academic librarians in Metro Manila - Macapagal, Karen I. (2001)
This study is about the job satisfaction levels among academic librarians in Metro Manila. Job satisfaction was grouped in two categories, job content which are aspects involved directly with work and job context which involves aspects outside of the actual work, extrinsic qualities. The author wanted to find out which aspects academic librarians feel more satisfied. Also, the preference among the nineteen dimensions included in both content and context aspects were ranked. There were five main hypotheses tested.